Investigation of Release Kinetics of DOX from Polydopamine Nanocapsules Prepared by Hard Template Method - Elahe Abdollahi; Vahid Haddadi‐Asl; Hanie Ahmadi; Mastoure Shirjandi; Fatemeh Khanipour (Macromolecular Materials and Engineering)
Abstract Development of smart drug delivery systems (DDSs) for effective delivering drugs to targeted areas and achieving controlled drug release (CDR) is critical for cancer chemotherapy. The purpose of this study is synthesis of polydopamine (PDA) nanocapsules and analyze the adsorption and release properties of doxorubicin (DOX). PDA nanocapsules are manufactured using hard template approach. The influence of various parameters such as pH, adsorption time, and initial DOX content on the adsorption and release process is investigated. The resulting adsorption isotherm is consistent with the Langmuir isotherm, indicating that DOX adsorption on PDA nanocapsules is homogenous, uniform, and monolayer. PDA nanocapsules have an adsorption capacity of 689.6 mg g−1 under alkaline conditions, which is attributed to phenol group deprotonation mechanism and electrostatic repulsion. The adsorption kinetics are more consistent with the pseudo‐second‐order model. Furthermore, raising initial concentration of DOX results in a greatly increased adsorption capacity due to a larger driving force. Among the several parameters that can influence the pace and degree of DOX loading and release, local pH is regarded as a significant environmental component in the processes. Thus, pH‐responsive PDA nanocapsules have a significant potential for usage in locations with aberrant pH level, such as cancer tissue.